Brain signatures: a modality for biometric authentication - Hema, Chengalvarayan Radhakrishnamurthy; Paulraj, Murugesapandian; Kaur, Harkirenjit (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org